Aberrant expression of acute-phase reactant proteins in sera and breast lesions of patients with malignant and benign breast tumors - Doustjalali, S.R.; Yusof, R.; Yip, C.H.; Looi, L.M.; Pillay, B.; Hashim, Onn Haji (2004)
We have analyzed unfractionated sera of newly diagnosed patients (n =10) with breast carcinoma (BC), prior to treatment, and patients (n = 5) with fibrocystic disease of the breast (FDB) by two-dimensional gel electrophoresis (2-DE) and silver staining. The patients' 2-DE serum protein profiles obtained were then subjected to image analysis and compared to similar data generated from sera of normal healthy female controls (n = 10) of the same range of age. The relative expression of alpha(1)-antichymotrypsin (ACT), clusterin, and complement factor B was significantly higher in all BC patients as compared to normal controls. However, the expression of alpha(1)-antitrypsin (AAT) in 4 BC patients was apparently lower than that of the controls. Similar differential expression of ACT was detected in the FDB patients. The aberrant expression of the serum acute-phase proteins of patients with BC and FDB was confirmed by competitive enzyme-linked immunosorbent assay (ELISA). Similar altered proteins expression was also observed from immunohistochemical studies of malignant (n = 5) and benign (n = 5) breast lesions of the respective patients performed using antisera to the aberrantly expressed proteins. However, the malignant breast lesions were instead positively stained for AAT The differential expression of the serum proteins was apparently abrogated when a six-month follow-up study was performed on nine of the BC patients subsequent to treatment.